Cell-penetrating Peptides as Keys to Endosomal Escape and Intracellular Trafficking in Nanomedicine Delivery - Soni, Sakshi; Kori, Shivam K.; Nema, Priyanshu; Iyer, Arun K.; Soni, Vandana; Kashaw, Sushil K. (Current Medicinal Chemistry, 2025)
This review article discusses the challenges of delivering cargoes to the cytoplasm, for example, proteins, peptides, and nucleic acids, and the mechanisms involved in endosomal escape. Endocytosis, endosomal maturation, and exocytosis pose significant barriers to effective cytoplasmic delivery. The article explores various endosomal escape mechanisms, such as the proton sponge effect, osmotic lysis, membrane fusion, pore formation, membrane destabilization/ disruption, and vesicle budding and collapse. Additionally, it discusses the role of lysosomes, glycocalyx, and molecular crowding in the cytoplasmic delivery process. Despite the recent advances in nonviral delivery systems, there is still a need to improve cytoplasmic delivery. Strategies such as fusogenic peptides, endosomolytic polymers, and cell-penetrating peptides have shown promise in improving endosomal escape and cytoplasmic delivery. More research is needed to refine these strategies and make them safer and more effective. In conclusion, the article highlights the challenges associated with cytoplasmic delivery and the importance of understanding the mechanisms involved in endosomal escape. A better understanding of these processes could result in the creation of greater effectiveness and safe delivery systems for various cargoes, including proteins, peptides, and nucleic acids.
Keywords: membrane fusion